2010
DOI: 10.1111/j.1365-2745.2010.01750.x
|View full text |Cite
|
Sign up to set email alerts
|

Crossing gradients of consumer pressure and physical stress on shallow rocky reefs: a test of the stress‐gradient hypothesis

Abstract: Summary1. The stress-gradient hypothesis predicts an increase in the importance and intensity of positive species interactions towards extreme ends of gradients generated by either physical stress or consumer pressure. However, little attention has been devoted to assessing how the co-occurrence of different gradients of stress and variations in the abundance of the benefactor can influence switches in species interactions. 2. On shallow rocky reefs, we assessed shifts in the effects of different covers of Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 54 publications
(86 reference statements)
2
47
0
Order By: Relevance
“…Also contradicting the predictions from the original SGH, studies in grazed ecosystems have reported an increase in facilitation intensity from low to high grazing pressure but a decrease again with further increases in grazing pressure (Smit et al, 2009). Such collapses in facilitation intensity at high grazing pressure have been observed in both terrestrial (Brooker et al, 2006;Graff et al, 2007;Saiz and Alados, 2012;Smit et al, 2007) and aquatic ecosystems (Bulleri et al, 2011;Le BagoussePinguet et al, 2012;Levenbach, 2009). Plants can protect neighbours by physically sheltering them from herbivore damage, but when grazing pressure becomes very high, facilitative interactions might wane, because the nurse itself gets damaged by grazing or trampling (Michalet et al, 2014), or because consumers might start searching more intensively for resources (Soliveres et al, 2011a).…”
Section: Introductionmentioning
confidence: 86%
“…Also contradicting the predictions from the original SGH, studies in grazed ecosystems have reported an increase in facilitation intensity from low to high grazing pressure but a decrease again with further increases in grazing pressure (Smit et al, 2009). Such collapses in facilitation intensity at high grazing pressure have been observed in both terrestrial (Brooker et al, 2006;Graff et al, 2007;Saiz and Alados, 2012;Smit et al, 2007) and aquatic ecosystems (Bulleri et al, 2011;Le BagoussePinguet et al, 2012;Levenbach, 2009). Plants can protect neighbours by physically sheltering them from herbivore damage, but when grazing pressure becomes very high, facilitative interactions might wane, because the nurse itself gets damaged by grazing or trampling (Michalet et al, 2014), or because consumers might start searching more intensively for resources (Soliveres et al, 2011a).…”
Section: Introductionmentioning
confidence: 86%
“…Facilitating tolerance of other biotic and abiotic stresses such as sea waves, pollination or dispersal stress has also been proposed as mechanisms of species interaction (Table 1). However, the cumulative effects of cooccurring environmental stresses, particularly abiotic and biotic stresses on species interactions, which may play an important role in community assembly are still poorly understood (Bulleri et al, 2011).…”
Section: Mechanisms Of Planteplant Facilitation In Coastal Wetlandsmentioning
confidence: 99%
“…concealment), in which neighbours reduce herbivory on focal individuals by making them less conspicuous or accessible ( [6], see [7] for a recent review). We know little about the relative strength of these two facilitative mechanisms, or how they interact, since few experimental studies incorporate both variable stress levels and herbivory ( [1], but see [4,8,9]). …”
Section: Introductionmentioning
confidence: 99%